2019
DOI: 10.1021/acs.jchemed.9b00375
|View full text |Cite
|
Sign up to set email alerts
|

Student-Designed Green Chemistry Experiment for a Large-Enrollment, Introductory Organic Laboratory Course

Abstract: A 3-week module incorporating the principles of green chemistry was developed for a large-enrollment, introductory organic chemistry laboratory course. An emphasis was placed on students planning their own experiments with the goal of obtaining a greener reaction (week 1). Students executed their designed experiments in week 2 and were given an opportunity to repeat the experiment or further optimize the reaction conditions to improve the yields during week 3. A postlab writing assignment as well as pre-and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 55 publications
0
25
0
3
Order By: Relevance
“…Supplementing core topics with sustainability has been achieved through the efforts of initiatives such as Green Chemistry Education. 68 While sustainable concepts and green chemistry have been primarily showcased in upper level elective 69,70 and organic chemistry lab courses, 71,72,73,74 efforts have been made to expand the curriculum into introductory 75,76,77 and general chemistry courses. 78,79,80 The lack of green chemistry content in organic chemistry textbooks has been explored and it has been suggested that connections to societal issues and sustainability contribute to the development of leadership skills.…”
Section: Key Takeawaysmentioning
confidence: 99%
“…Supplementing core topics with sustainability has been achieved through the efforts of initiatives such as Green Chemistry Education. 68 While sustainable concepts and green chemistry have been primarily showcased in upper level elective 69,70 and organic chemistry lab courses, 71,72,73,74 efforts have been made to expand the curriculum into introductory 75,76,77 and general chemistry courses. 78,79,80 The lack of green chemistry content in organic chemistry textbooks has been explored and it has been suggested that connections to societal issues and sustainability contribute to the development of leadership skills.…”
Section: Key Takeawaysmentioning
confidence: 99%
“…Praktikum memberi siswa pengalaman untuk membuktikan diri secara langsung tentang apa yang telah mereka pelajari, seperti keterampilan proses sains sesuai dengan karakteristik sains itu sendiri. Pelaksanaan praktikum lebih baik daripada hanya mendengarkan ceramah di kelas tentang diskusi suatu ilmu pengetahuan, sehingga pembelajaran akan lebih bermakna (Wu et al, 2019). Laboratorium didefinisikan sebagai: a) tempat pelatihan ilmiah, termasuk; praktikum dan kegiatan lain yang membantu mahasiswa memperoleh keterampilan ilmiah, b) sebuah lokakarya di mana ilmu pengetahuan faktual dilakukan atau di mana kegiatan ilmiah dilakukan di bawah lingkungan yang kondusif, c) termasuk partisipasi dalam berbagai kegiatan praktikum, pengamatan dan demonstrasi yang memberikan peluang untuk peserta didik untuk mengembangkan pemahaman konsep praktis dan teoritis melalui pemecahan masalah (Gonçalves et al, 2019).…”
Section: Pendahuluanunclassified
“…Kimia organik melalui praktik di laboratorium diyakini dapat meningkatkan pemahaman konseptual kimia organik sesuai dengan apa yang telah mereka pelajari di kelas, diikuti dengan peningkatan pengembangan keterampilan praktik (Supasorn, 2012). Praktikum kimia organik yang selama ini dilakukan masih membutuhkan banyak perbaikan, khususnya pada metode pembelajaran di laboratorium, karena masih kurangnya penguasaan konsep mahasiswa saat menyelesaikan perkuliahan di praktikukm kimia organik (Akani, 2015;Costantino & Barlocco, 2019;Mancheño et al, 2019;Pontrello, 2016;Wu et al, 2019).…”
Section: Pendahuluanunclassified
“…Since then, many advances have been made in the chemical industry to minimize the consumption of water and energy, and also the amount of waste produced. Additionally, some of these concepts have been introduced in several undergraduate and postgraduate programs [22][23][24][25], including in the organization of education institutions [26,27], although they are still far from becoming systemically infused into the undergraduate chemistry and engineering curricula [28]. Other important tool is LCA (Life Cycle Assessment), which provides a quantitative assessment of the environmental impact of products over their entire life cycle, with a view to making improvements [29].…”
Section: Introductionmentioning
confidence: 99%